Low-cost supercapacitor based on colloidal graphite - Dos Santos Klem, Maykel [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Alves, Neri [UNESP] (FapUNIFESP (SciELO), 2021)
Here we report the production and characterization of a low-cost supercapacitor with electrodes based on colloidal graphite. We characterized the as-prepared device in terms of cyclic voltammetry (CV), Galvanostatic charge/discharge (GCD), and impedance spectroscopy. The supercapacitor exhibited good electrochemical performance with a high capacitance of 22 F g-1for a discharge current of 2 mA. Long-term cyclability tests show that the device can keep about 85% of its capacitance after 500 cycles, even without encapsulation. We found power and energy densities of 110 W kg-1and 3 Wh kg-1, respectively. All the experimental results indicate that the colloidal graphite Aquadag® is a promising material for application in supercapacitors.
Keywords: Aquadag; Colloidal Graphite; Energy Storage; Supercapacitor